Soluble and functional expression of a recombinant enantioselective amidase from Klebsiella oxytoca KCTC 1686 in Escherichia coli and its biochemical characterization. Issue 8 (August 2015) - Guo, Fa-Mou; Wu, Jian-Ping; Yang, Li-Rong; Xu, Gang
Graphical abstract: Highlights: An amidase gene was functionally expressed in E. coli without affinity tag. Affinity tag affected the soluble expression and activity of KamH. Amidases containing N-terminal α-helical domain may be expressed in this strategy. KamH has a wide substrate spectrum and strict ( S )-enantioselectivity. Abstract: A gene encoding an enantioselective amidase (KamH) was cloned from Klebsiella oxytoca KCTC 1686 and inserted into the Eco RI and Hin dIII sites of the vector pET-30a(+). When KamH with a peptide containing a His-tag and an enterokinase cleavage site was overexpressed in Escherichia coli, approximately half was found in the soluble fraction, but it lacked activity. After cleavage of the peptide by enterokinase, the enzyme activity was partly restored, reaching 420.2 ± 33.62 U/g dry cell weight (DCW). Another recombinant plasmid was constructed by inserting the KamH gene into the Nde I and Eco RI sites of pET-30a(+) to express KamH in its native form. The overexpressed amidase was found primarily in the soluble fraction and its maximum activity was 3613.4 ± 201.68 U/g DCW. This indicated that the peptide influenced not only soluble expression but also activity of KamH, perhaps by blocking the substrate-binding tunnel of KamH. Similar results were obtained with heterologously expressed amidases from Rhodococcus erythropolis MP50 and Agrobacterium tumefaciens d3. All of these amidases have an N-terminal α-helical domain. Therefore, amidases of this type may be functionally expressed in their native form. KamH hydrolyzed a range of aliphatic and aromatic amides and exhibited strict S -selectivity towards racemic amides.